Haemophilus influenzae-protein D specific antibody correlate with protection against acute otitis media in young children. Issue 9 (21st February 2018) - Almudevar, Anthony; Pichichero, Michael E.
Abstract: Background: Haemophilus influenzae ( Hi ) causes respiratory infections and pathogenesis of this microbe begins in the human nasopharynx (NP). The objective of this study was to assess the correlation of NP colonization-induced serum antibody levels to Hi protein D with risk of acute otitis media (AOM) in children <2 yr. Methods: 455 sera from 213 children (age 6–24 months old) were collected when they were colonized with Hi and when the children developed AOM. Presence of Hi during AOM was confirmed by culture of middle ear fluid. Quantitative ELISA was used to determine serum IgG against protein D antigen. Results: Asymptomatic Hi NP colonization reduced the risk of future AOM infections. Higher serum IgG titers against Hi protein D were correlated with reduced future AOM risk. Conclusion: Colonization by Hi reduces future AOM risk. Higher antibody levels against protein D correlates with lower risk of AOM caused by Hi .